Chariots of fire - Hudson, Hugh.; Puttnam, David, 1941-; Welland, Colin; Farrell, Nicholas; Havers, Nigel, 1949-; Charleson, Ian.; Cross, Ben.; Gerroll, Daniel; Holm, Ian, 1931-2020.; Gielgud, John, 1904-2000.; Anderson, Lindsay, 1923-1994.; Davenport, Nigel; et al. (Burbank, CA : Warner Home Video, 2010)
The story, told in flashback, of two young British sprinters competing for fame in the 1924 Olympics. Eric, a devout Scottish missionary runs because he knows it must please God. Harold, the son of a newly rich Jew runs to prove his place in Cambridge society. In a warmup 100 meter race, Eric defeats Harold, who hires a pro trainer to prepare him. Eric, whose qualifying heat is scheduled for a Sunday, refuses to run despite pressure from the Olympic committee. A compromise is reached when a nobleman allows Eric to compete in his 400 meter slot. Eric and Harold win their respective races and go on to achieve fame as missionary and businessman/athletic advocate, respectively.
DVD; Region 1; 5.1 Dolby Digital surround, Dolby Digital mono.; widescreen presentation widescreen presentation preserving the aspect ratio of its original theatrical exhibition, 1.85:1, enhanced for 16X9 widescreen televisions.
In English or dubbed French with optional subtitles in English, French, or Spanish; closed-captioned.
Nicholas Farrell (Aubrey Montague), Nigel Havers (Lord Andrew Lindsay), Ian Charleson (Eric Liddell), Ben Cross (Harold Abrahams), Daniel Gerroll (Henry Stallard), Ian Holm (Sam Mussabini), John Gielgud (Master of Trinity), Lindsay Anderson (Master of Caius), Nigel Davenport (Lord Birkenhead), Cheryl Campbell (Jennie Liddell), Alice Krige (Sybil Gordon), Dennis Christopher (Charles Paddock), Brad Davis (Jackson Scholz), Patrick Magee (Lord Cadogan), Peter Egan (Duke of Sutherland), Struan Rodger (Sandy McGrath), David Yelland (Prince of Wales), Yves Beneyton (George Andre).
Director of photography, David Watkin ; camera operator, Dewi Humphreys ; editor, Terry Rawlings ; original music composed, arranged, and performed by Vangelis Papathanassioli ; supervising art director, Roger Hall ; costume designer, Milena Canonero ; athletic consultant, Tom McNab.
Originally produced as a British motion picture in 1981.
Winner, 1982 BAFTA (British Academy of Film and Television Arts) Film Awards for Best Costume Design: Milena Canonero; Best Supporting Artist: Ian Holm; Best Film: David Puttnam; 1982 Academy Awards for Best Costume Design: Milena Canonero; Best Music, Original Score: Vangelis; Best Writing, Screenplay Written Directly for the Screen: Colin Welland; Best Picture: David Puttnam. Winner of four 1981 Academy Awards.
Keywords: Abrahams, Harold Maurice, -- 1899-1978 -- Drama; Liddell, Eric, -- 1902-1945 -- Drama; Track and field athletes -- Biography -- Drama; Cross-country running -- Drama; Christian life -- Drama; Jewish athletes -- Drama; Video recordings for hard of hearing people; England -- Social life and customs -- Drama; Great Britain -- History -- 20th century -- Drama; Sports films; Feature films